ISSUES OF IMPLEMENTATION OF TERMS RELATED TO THE RAILWAY SECTOR IN THE ENGLISH LANGUAGE TEACHING PROCESS - Botirova Nilufar Salimjon kizi (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2024)
This article is about the educational process of future specialists the process of working with the terminology of the railway sector is considered. Railway the classification of terms related to the field and the procedure for its application are explained. English railway terminology is distinguished by its content and structural features, linguistic point of view. It is part of the lexicon of the language. Methodology of teaching a foreign language is a component of linguodidactics, and when teaching terms, their linguistic the importance of features is discussed.